FENOMENA PERATAAN LABA DI INDONESIA: GARBLING VS SIGNALLING - Pratiwi, Setha Octatiasari; Mahastanti, Linda Ariany (AMONG MAKARTI, 2013)
Abstract The purpose of this study is to analyze whether the phenomenon of income smoothing in Indonesia is signalling or garbling. The sample in this study was 10 manufacture companies which released financial statement since 2010-2012 and published obligation. Using Tucker and Zarowin’s income smoothing statistic, this study discovered companies with high level of income smoothing and companies with low level of income smoothing. Descriptive statistic test with mean, maximum and minimum analysis tools were used in this study to analyze the difference between companies with high yield and companies with low yield and to analyze the difference of company characteristics of companies with signaling income smoothing and companies with garbling income smoothing. Study results showed that the income smoothing phenomenon in Indonesia tended to be garbling. It showed that investors in Indonesia were more selective in making investment decision. Keywords: income smoothing, cost of debt, garbling, signalling, profit